2007
DOI: 10.1111/j.1460-9568.2007.05640.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony‐stimulating factor has a negative effect on stroke outcome in a murine model

Abstract: The administration of CD34-positive cells after stroke has been shown to have a beneficial effect on functional recovery by accelerating angiogenesis and neurogenesis in rodent models. Granulocyte colony-stimulating factor (G-CSF) is known to mobilize CD34-positive cells from bone marrow and has displayed neuroprotective properties after transient ischemic stress. This led us to investigate the effects of G-CSF administration after stroke in mouse. We utilized permanent ligation of the M1 distal portion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 30 publications
1
52
0
Order By: Relevance
“…In brief, the left MCA was isolated, electrocauterized, and disconnected just distal to its crossing of the olfactory tract (distal M1 portion) under halothane inhalation. The infarct area in mice of this background has been shown to be highly reproducible and limited to the ipsilateral cerebral cortex [8,15,33,34].…”
Section: Induction Of Focal Cerebral Ischemiamentioning
confidence: 99%
See 2 more Smart Citations
“…In brief, the left MCA was isolated, electrocauterized, and disconnected just distal to its crossing of the olfactory tract (distal M1 portion) under halothane inhalation. The infarct area in mice of this background has been shown to be highly reproducible and limited to the ipsilateral cerebral cortex [8,15,33,34].…”
Section: Induction Of Focal Cerebral Ischemiamentioning
confidence: 99%
“…Permanent focal cerebral ischemia was produced by ligation and disconnection of the distal portion of the left middle cerebral artery (MCA) [8,15,33,34]. In brief, the left MCA was isolated, electrocauterized, and disconnected just distal to its crossing of the olfactory tract (distal M1 portion) under halothane inhalation.…”
Section: Induction Of Focal Cerebral Ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Once pre-specified exclusion criteria were applied, a total of 19 publications were chosen for analysis (table 1); these came from 12 laboratories in 8 countries (China, France, Germany, Japan, South Korea, Taiwan, UK and USA). Only one negative study was identified in which G-CSF had a detrimental effect on behavioural function, caused brain atrophy and exaggerated the inflammatory response in the infarcted area (Taguchi et al, 2007). Studies excluded (table 2) were those administering G-CSF in combination with other agents such as stem cell factor (SCF) and those assessing chronic (i.e.…”
Section: Design Of Studiesmentioning
confidence: 99%
“…G-CSF significantly reduced neurological deficit (SMD -1.37, 95% CI -2.13 to -0.61, p=0.0004) in 11 studies (Komine-Kobayashi et al, 2006;Sehara et al, 2007a;Sevimli et al, 2009;Solaroglu et al, 2009;Taguchi et al, 2007;Yanqing et al, 2006). Impairment was measured at various time points post stroke (1, 2, 3, 7, 14, 21 and 35 days); beneficial effects of G-CSF were seen at all times but there was no correlation between reduction in impairment and time to measurement (r s = 0.37, p=0.47).…”
Section: Motor Impairmentmentioning
confidence: 99%